Concept of “Quality” in Higher Education: From Offline to Online Mode - A. E. Korchak; T. E. Khavenson (Высшее образование в России)
Quality concept, due to its multifaceted and polyfunctional nature, is in use in different areas. The term started its way in the field of higher education in 1980s, but numerous discussions on how to define it have been ongoing ever since. Considering rapid growth of online practices in universities and the fact that there is still no conventional system of quality assurance and evaluation for online mode, the aforementioned problems are becoming even more topical. In the article with an aim to grasp meaning of quality online, its theoretical and practical levels are correlated. Papers summarizing traditional approaches to rethinking quality concept in higher education and tools of practical work with quality in online and offline modes are selected as a basis for analysis. A transition from dissipated definitions into the systems of their aggregation is traced. Elements of quality understanding in offline mode potentially applicable to online are identified. The main differences between categories of quality assurance in online and offline are outlined, along with the mechanisms of their portability from one mode to another. Basing on the analysis conducted, an approach of working with quality of university online programmes synchronizing theoretical and practical levels is offered. This paper may be of interest for researchers in the field of higher education and university managers, whose interests concern questions of internal quality assurance and quality culture.